2017
DOI: 10.1097/cco.0000000000000367
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of protein translation as a new treatment paradigm for prostate cancer

Abstract: Purpose of review This overview will summarize some of the developments in the area of protein translation, including as they relate to the therapeutic targeting of prostate cancer. Recent findings Translational control, mediated by the rate-limiting eukaryotic translation initiation factor 4E (eIF4E), drives selective translation of several oncogenic proteins, thereby contributing to tumor growth, metastasis, and treatment resistance in various cancers, including prostate cancer. As an essential regulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 97 publications
1
23
0
Order By: Relevance
“…A rise in serum PSA, which is partly related to f-AR transcriptional activity, serves as an index of CRPC growth and progression [23]. Interestingly in the present study, in vivo administration of VNLG-152 down-regulated the expression of both the f-AR and f-AR splice variants, with more potency Enhanced activation of eIF4E is another common feature in advanced prostate cancer [27][28][29][30]. In the nucleus, eIF4E associates with a subset of mRNAs containing '4E-sensitivity elements' in their 3 0 -untranslated regions and promotes their export through nuclear pores.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…A rise in serum PSA, which is partly related to f-AR transcriptional activity, serves as an index of CRPC growth and progression [23]. Interestingly in the present study, in vivo administration of VNLG-152 down-regulated the expression of both the f-AR and f-AR splice variants, with more potency Enhanced activation of eIF4E is another common feature in advanced prostate cancer [27][28][29][30]. In the nucleus, eIF4E associates with a subset of mRNAs containing '4E-sensitivity elements' in their 3 0 -untranslated regions and promotes their export through nuclear pores.…”
Section: Discussionmentioning
confidence: 45%
“…Enhanced activation of eIF4E is another common feature in advanced prostate cancer . In the nucleus, eIF4E associates with a subset of mRNAs containing ‘ 4E‐sensitivity elements ’ in their 3′‐untranslated regions and promotes their export through nuclear pores.…”
Section: Discussionmentioning
confidence: 99%
“…It was rationally designed as an inhibitor of androgen biosynthesis via inhibition of 17α-hydroxylase/17,20-lyase (CYP17), the key enzyme which catalyzes the biosynthesis of androgens from the progestins. Through extensive and rigorous preclinical studies, galeterone was shown to modulate two other targets in the androgen/androgen receptor (AR) signaling pathway [11] and shown to inhibit the eukaryotic initiation factor 4E (eIF4E) protein translational machinery [49]. Galeterone advanced successfully through phases I and II clinical trials in prostate cancer patients but was unsuccessful in the pivotal phase III clinical trial in men with castration-resistant prostate cancer (CRPC), harboring AR splice variants (e.g., AR-V7).…”
Section: Galeterone (5)mentioning
confidence: 99%
“…There has been increasing interest in the development of agents that inhibit oncogenic eIF4F translation complex as strategy to obtain effective anticancer therapeutics against a variety of solid tumors and hematologic cancers (Bhat et al, 2015;Pelletier et al, 2015;Pettersson et al, 2015;Pettersson et al, 2014;Pettersson et al, 2011;Ramamurthy et al, 2017). Amongst the various strategies of disrupting eIF4F complex (and as a consequent, eIF4E), inhibition of Mnk1/2 to prevent phosphorylation of eIF4E is generating keen interest, evidenced by the increasing number of research publications and patents/patent applications (reviewed in ref.…”
Section: Introductionmentioning
confidence: 99%
“…Our group recently discovered a class of novel retinamides (NRs; semi-synthetic natural products), small molecule Mnk1/2 protein degraders that potently inhibit Mnk-eIF4E and mTORC1/4E-BP1/p70SK6 oncogenic signaling in breast and prostate cancer models (Mbatia et al, 2015;Ramalingam et al, 2014;Ramamurthy et al, 2015;Ramamurthy et al, 2017). NRs exert potent anticancer effects in breast and prostate cancer cells and tumor xenografts by inducing ubiquitin-proteasomal degradation of Mnk1/2 and preventing eIF4E and mTORC1 activation, thereby leading to inhibition of cancer cell growth, apoptosis evasion, cell migration and invasion, in vitro and inhibition of tumor xenografts, in vivo (Mbatia et al, 2015;Ramalingam et al, 2014;Ramamurthy et al, 2015;Ramamurthy et al, 2017). Among various NRs, lead racemic VNLG-152 (termed VNLG-152R; 4-(±)-(1H-imidazol-1-yl)-N-(4-fluorophenyl)-(E)-retinamide; Figure 1A) exhibited exemplary Mnk-eIF4E/m-TORC1 inhibitory and in vitro anticancer activities in a variety of breast cancer subtypes (Ramalingam et al, 2014).…”
Section: Introductionmentioning
confidence: 99%